2019
DOI: 10.2478/johh-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Finding behavioral parameterization for a 1-D water balance model by multi-criteria evaluation

Abstract: Evapotranspiration is often estimated by numerical simulation. However, to produce accurate simulations, these models usually require on-site measurements for parameterization or calibration. We have to make sure that the model realistically reproduces both, the temporal patterns of soil moisture and evapotranspiration. In this study, we combine three sources of information: (i) measurements of sap velocities; (ii) soil moisture; and (iii) expert knowledge on local runoff generation and water balance to define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…The differences in model behavior due to soil parameterizations through different PTFs were already analyzed in a study by [58] using a 1D hydrological model. They showed that even when the very same soil was considered in the entire parameterization scheme, and simulated transpiration and soil moisture were consistent with observations, yet the runoff processes or total water balance could be estimated incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in model behavior due to soil parameterizations through different PTFs were already analyzed in a study by [58] using a 1D hydrological model. They showed that even when the very same soil was considered in the entire parameterization scheme, and simulated transpiration and soil moisture were consistent with observations, yet the runoff processes or total water balance could be estimated incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…Evapotranspiration plays an important role in the estimation of the water balance on many hydrologically relevant spatial and temporal scales (Casper et al, 2019). Without measuring evaporation and transpiration on the field scale, which is complicated due to the extreme heterogeneity of the whole relevant factors in the environment, the upscaling of point measurements to hillslope, catchment and regional scales cannot be completed (Burt et al, 2005).…”
Section: Recent Advances In the Hydrology Of The Carpathian Basinmentioning
confidence: 99%